9 SUPERIOR VENA CAVA SYNDROME MASKING B-CELL LYMPHOMA: A LIKELY SEQUELA OF THE CHERNOBYL NUCLEAR DISASTER. Issue 1 (1st January 2007) - Atwal, P.; Shah, R.; Atwal, C.; Gali, L.; Niranjan, S.
Abstract : Partial or complete obstruction of the thin-walled superior vena cava (SVC) is a relatively rare condition. The patients may present with swelling of the neck and face, headache, dizziness, visual disturbances, stupor, and syncope. The cutaneous veins of the upper chest and lower neck may become dilated and flushing of the face and neck may develop. The most frequent causes of SVC obstruction are divided into two categories: (1) non-neoplastic (mediastinitis, constrictive pericarditis, histoplasmosis, etc) and (2) neoplastic (superior mediastinal tumors). B-cell lymphoma, a subtype of non Hodgkin's lymphoma, is one of the mediastinal tumors that can cause SVC obstruction. Most common symptoms of B-cell lymphoma are fever with night sweats, weight loss, and fatigue, but rarely it may give a unique presentation of SVC syndrome. A 41-year-old Ukrainian female presented with the history of swelling of the face, neck, left arm, left hemithorax, facial flushing, and generalized body aches. Her past medical history was significant for exposure to radiation during the Chernobyl nuclear disaster. On physical examination, the patient had jugular venous distention with dilated anterior chest wall veins. Chest radiography revealed a widened mediastinum. CT scan of the chest revealed an anterior mediastinal mass with compression of the proximal SVC and left innominate vein. A mediastinotomy was performed and a biopsy of the mass and bone marrow revealed a large B-cell lymphoma infiltrating the bone marrow. The patient was given eight cycles of CHOP therapy (cyclophosphamide, Adriamycin, vincristine, prednisone) with rituximab. With this treatment, the patient went into remission. The etiology of B-cell lymphoma has been considered multifactorial, and exposure to radiation has also been hypothesized as one of the causes. Ionizing radiation exposure may result in multiple neoplastic diseases, including leukemia and cancers of the skin, breast, lung, and thyroid. Although there is no definite etiology, it is very likely in this case that radiation exposure during the Chernobyl nuclear disaster resulted in the B-cell lymphoma in this patient, leading to a unique presentation of SVC syndrome. If a timely diagnosis is made and combination chemotherapy instituted, patients may achieve complete remission and long-term survival is possible.